A fluorimetric method for the measurement of pyridoxal and pyridoxal phosphate in human plasma and leucocytes, and its application to patients with sideroblastic marrows. Issue 6 (June 1983) - Smith, G P; Samson, D; Peters, T J
Abstract : A highly sensitive fluorimetric assay for the measurement of pyridoxal and pyridoxal phosphate in biological tissues is described. The method involves the enzymic hydrolysis of pyridoxal phosphate to pyridoxal. The pyridoxal (free or total) is separated on an anion-exchange column, concentrated by cation-exchange chromatography and reacted with potassium cyanide under slightly alkaline conditions to form 4-pyridoxolactone, a highly fluorescent compound. The method is applied to the measurement of pyridoxal, pyridoxal phosphate and total pyridoxal in plasma and neutrophils from control subjects and patients with sideroblastic marrow and identified the patient with pyridoxine-responsive sideroblastic anaemia.